Development of Hematopoietic Stem and Progenitor Cells from Human Pluripotent Stem Cells() - Chen, Tong (J Cell Biochem, 2015)
Human pluripotent stem cells (hPSCs), including human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs), provide a new cell source for regenerative medicine, disease modeling, drug discovery, and preclinical toxicity screening. Understanding of the onset and the sequential process of hematopoietic cells from differentiated hPSCs will enable the achievement of personalized medicine and provide an in vitro platform for studying of human hematopoietic development and disease. During embryogenesis, hemogenic endothelial cells, a specified subset of endothelial cells in embryonic endothelium, are the primary source of multipotent hematopoietic stem cells. In this review, we discuss current status in the generation of multipotent hematopoietic stem and progenitor cells from hPSCs via hemogenic endothelial cells. We also review the achievements in direct reprogramming from non-hematopoietic cells to hematopoietic stem and progenitor cells. Further characterization of hematopoietic differentiation in hPSCs will improve our understanding of blood development and expedite the development of hPSC-derived blood products for therapeutic purpose. This article is protected by copyright. All rights reserved